Self-expandable biodegradable biliary stents in porcine model - Grolich, Tomáš; Crha, Michal; Novotný, Ladislav; Kala, Zdeněk; Hep, Aleš; Nečas, Alois; Hlavsa, Jan; Mitáš, Ladislav; Misík, Jan (The Journal of surgical research, 2015)
BACKGROUND: Treatment or prevention of a benign biliary tree stricture is an unresolved problem. A novel self-expandable biodegradable polydioxanon biliary stent in a porcine model was studied. MATERIALS AND METHODS: This new stent was used in 23 pigs. Feasibility and safety of surgical stenting, time of biodegradation, and histologic reaction in 2, 8, 13, and 20 wk of a follow-up were studied. All stents were inserted into a common bile duct through a duodenal papilla following small dilatation. After surgical evaluation of abdominal cavities, the pigs were sacrificed to remove common bile ducts with the stents. All bile ducts were assessed by macroscopic and histopathologic examination. RESULTS: Self-expansion was correct in all cases. Neither bile duct obstruction nor postsurgical complications were observed. Macroscopic evaluation indicated lightening of the stent color in 2 wk, a partial disintegration in 8 wk, and a complete absorption in 13 and 20 wk. Histologic evaluation in general substantiated a mild-to-moderate inflammatory reaction in the lamina propria during the whole follow up and had no clinical consequences. No cholangitis, necrosis, abscess, or excessive fibroplasia was found in a hepatoduodenal ligament. CONCLUSIONS: Our results suggest that polydioxanon biodegradable self-expanding stents seem to be useful for biliary system implantation, offer a good biocompatibility, and completely degrade within 13 wk.
Keywords: stenty; studie proveditelnosti; Bile Duct Diseases; Female; chirurgie žlučových cest; zvířata; Biliary Tract Surgical Procedures; Biodegradable stent; Swine; Biocompatible Materials; Stents; ženské pohlaví; nemoci žlučových cest; Polydioxanon; prasata; biokompatibilní materiály; Animals; Feasibility Studies; Constriction, Pathologic; Biliary tree; stenóza